Global Interreligious Dialogue: Diplomasi Kultural Dalam Kebijakan Dialog Agama Bilateral Indonesia - Tyas Pramudita Indraning (Universitas Negeri Medan, 2020)
This study analyse Indonesia's cultural diplomacy through inter-state religious dialogue. Specifically, this study aims to find out the background of Indonesian cultural diplomacy, bilateral dialogue between religions and cultures and Indonesian bilateral diplomacy. Diplomacy is a way, with certain manners, that is used by a country to achieve the country's national interests in relations with other countries or with the international community. In the context of the former effectiveness of diplomacy, it requires political or economic support or a real economic, political, and military power, but now we know what is called cultural diplomacy, which in fact economic, political and military forces in certain cases is